Measuring Uncertainty of a Combined Forecast and Some Tests for Forecaster Heterogeneity - Kajal Lahiri; Huaming Peng; Xuguang Sheng (Center for Economic Studies and ifo Institute (CESifo), 2015)
We have argued that from the standpoint of a policy maker, the uncertainty of using the average forecast is not the variance of the average, but rather the average of the variances of the individual forecasts that incorporate idiosyncratic risks. With a slight reformulation of the loss function and a standard factor decomposition of a panel of forecasts, we show that the uncertainty of the average forecast can be expressed as the disagreement among the forecasters plus the volatility of the common shock. Using new statistics to test for the homogeneity of idiosyncratic errors under the joint limits with both T and n approaching infinity simultaneously, we show that some previously used measures significantly underestimate the conceptually correct benchmark forecast uncertainty.
Keywords: C12; C33; E37; 330; forecast combination; forecast uncertainty; model averaging; panel data